Clean energy innovation in China: Fact and fiction, and implications for the future - Anders Hove (The Oxford Institute for Energy Studies, 2024)
With the Biden administration in the US introducing tariffs on Chinese clean energy and electric vehicle (EV) goods and components, and the European Union (EU) also imposing duties on electric vehicles because of Chinese state support for these industries, the narrative around China's dominance in clean energy manufacturing is fixated on the uneven playing field afforded by government largesse. Such narratives are simplistic and underplay the complex combination of factors that have led to China's rise in cleantech as a dominant producer. For countries and companies looking to engage and/or compete with China, it is important to recognize that competing in wind, solar PV, batteries, and EVs requires process-level innovation, which in turn requires mastery of, and ongoing interaction with, the entire supply chain. While basic R&D spending and top-notch universities will remain important, the benefits of such research may not always flow into the hands of domestic players. China's EV, battery, and solar firms are able to innovate and scale up output quickly in part because of the important role of vertical integration and manufacturing clusters. Vertical integration and clustering appears to benefit the type of innovation - namely, in manufacturing and related processes - that yields a competitive advantage in these fields.
Keywords: 330; batteries; China; clean energy; electric vehicles; industrial policy; innovation; Renewable Energy